Identification of Asymmetric DDoS Attacks at Layer 7 with Idle Hyperlink - Sood, Kiran; Dev, Maha; Singh, Khushwant; Singh, Yudhvir; Barak, Dheerdhwaj (ECS transactions, 2022)
Asymmetric denial-of-service (DDoS) attacks have become very complicated to deal with because of the use of several Internet Protocol (IP) addresses in these types of attacks. The purpose of research is different strategies are used by an attacker to achieve the objective of forcing the unavailability of the targeted server. Sometimes the large size of the file is used with a higher transfer rate so that the targeted website could be hanged for a legitimate customer. The design of a novel mechanism, in the form of Dynamic Honey Link (DHL), to prevent identification by sophisticated DDoS attacking tools, the findings this developed here for the detection of asymmetric attacks. Parameters such as IP addresses, Time of Request, and difference of time between requests of IPs are used in this mechanism and are verified applying correlation coefficients and p-values. This new analysis of different website attacks using an analysis of dataset leads to inspection and identification of hyperlinks.